Thermoresponsive Gels with Rosemary Essential Oil: A Novel Topical Carrier for Antimicrobial Therapy and Drug Delivery Applications - Ludovic Everard Bejenaru; Adina-Elena Segneanu; Cornelia Bejenaru; Ionela Amalia Bradu; Titus Vlase; Dumitru-Daniel Herea; Marius Ciprian Văruţ; Roxana Maria Bălăşoiu; Andrei Biţă; Antonia Radu; George Dan Mogoşanu; Maria Viorica Ciocîlteu (Gels)
This study investigates the development and comprehensive characterization of innovative thermoresponsive gels incorporating rosemary essential oil (RoEO) encapsulated in poly(lactic-co-glycolic acid) (PLGA) microparticles, with a focus on their potential applications in topical antimicrobial and wound healing therapies. RoEO, renowned for its robust antimicrobial, antioxidant, and wound-healing properties, was subjected to detailed chemical profiling using gas chromatography-mass spectrometry (GC–MS), which identified oxygenated monoterpenes as its dominant constituents. PLGA microparticles were synthesized through an optimized oil-in-water emulsion technique, ensuring high encapsulation efficiency and structural integrity. These microparticles were thoroughly characterized using Fourier-transform infrared (FTIR) spectroscopy to confirm functional group interactions, scanning electron microscopy (SEM) for surface morphology, X-ray diffraction (XRD) for crystalline properties, and thermal analysis for stability assessment. The synthesized microparticles displayed uniform size distribution and efficient encapsulation, demonstrating compatibility with the gel matrix. Two distinct thermoresponsive gel formulations were developed using varying ratios of Poloxamer 407 and Poloxamer 188 to achieve optimal performance. The gels were evaluated for key physicochemical properties, including pH, gelation temperature, viscosity, and rheological behavior. Both formulations exhibited thermoresponsive gelation at skin-compatible temperatures (27.6 °C and 32.9 °C), favorable pH levels (6.63 and 6.40), and shear-thinning behavior suitable for topical application. Antimicrobial efficacy was assessed against common pathogens associated with skin infections, including Staphylococcus aureus, Escherichia coli, and Candida albicans. The RoEO-PLGA-loaded gels demonstrated significant inhibitory effects, confirming their potential as effective carriers for controlled and localized drug delivery. These findings underscore the promising application of RoEO-PLGA-loaded thermoresponsive gels in addressing challenges associated with topical antimicrobial therapies and wound care, offering an innovative approach to enhancing therapeutic outcomes. By integrating the bioactive potential of RoEO with the advanced delivery capabilities of PLGA microparticles and thermoresponsive gels, this study paves the way for the development of next-generation formulations tailored to meet the specific needs of localized drug delivery in skin health management.